Propaganda Dalam Kampanye Boikot Produk dan Merek di Indonesia Antara Kesadaran Kolektif dan Manipulasi Ideologis - N, Nurhasanah; Haloho, Jessica Imanuel; Annasya, Syahira; Junianty, Dena (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The phenomenon of boycott campaigns against certain products and brands in Indonesia, particularly in the context of the Palestine-Israel conflict, reflects the significant role of propaganda in shaping public opinion. This study aims to examine how propaganda serves as both a tool for building collective awareness and a medium for ideological manipulation in society. Employing a descriptive qualitative approach, this research analyzes boycott narratives disseminated through online and social media platforms. The findings reveal that propaganda operates effectively through media framing, moral authority, and the exploitation of collective emotions such as anger and empathy. Nevertheless, it also indicates the presence of hegemonic processes infiltrating public discourse, potentially oversimplifying complex issues into dangerous moral dichotomies. This study highlights the urgency of media literacy and critical awareness towards boycott narratives to prevent society from being trapped in manipulative information flows. Propaganda, in this regard, functions as both a means of constructing consciousness and an ideological instrument that must be critically addressed within Indonesia’s digital public sphere.